2018
DOI: 10.1111/tri.13357
|View full text |Cite
|
Sign up to set email alerts
|

Association between donor age and risk of graft failure after liver transplantation: an analysis of the Eurotransplant database

Abstract: Summary Grafts from elderly donors are increasingly used for liver transplantation. As of yet there is no published systematic data to guide the use of specific age cutoffs the effect of elderly donors on patient outcomes must be clarified. This study analyzed the Eurotransplant database (01/01/2000–31/07/2014; N = 26 294) out of whom 8341 liver transplantations were filtered to identify for this analysis. 2162 of the grafts came from donors >60 including 203 from octogenarians ≥80 years. Primary outcome was t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 29 publications
0
18
0
1
Order By: Relevance
“…After prolonged cold ischemia, outcome of a graft depends on its ability to recover from the ischemia injury, which appears to be especially difficult in steatotic grafts or grafts from older donors (12)(13)(14). CIT influenced graft and patient survival in a linear fashion and only during the first year after transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…After prolonged cold ischemia, outcome of a graft depends on its ability to recover from the ischemia injury, which appears to be especially difficult in steatotic grafts or grafts from older donors (12)(13)(14). CIT influenced graft and patient survival in a linear fashion and only during the first year after transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…The mean age of liver donors is increasing worldwide, despite evidence that advanced donor age impacts early mortality after transplantation, mainly because of increased cellular senescence and reduced regeneration of hepatocytes [3,28,29]. The liver parenchyma is more vulnerable to ischemia-reperfusion injury and inflammatory cytokine responses before and after transplantation [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…Nagai et al reported twofold increased risk of hazard for CIT longer than 10 h and median time to HCC recurrence of 0.9 years [37]. After an extended CIT, graft outcome depends on the ability of the transplanted liver to recover from ischemia, which might be difficult in grafts from older donors [28,29,30,38]. Consequently, organs with longer CIT are often discarded because they are considered unsuitable for transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…We read with great interest the study by Pratschke et al [1] "Association between donor age and risk of graft failure after liver transplantation: An analysis of the Eurotransplant database." The study analyzed a large dataset from Eurotransplant and included a final sample of 8351 patients undergoing liver transplantation between January 2000 and July 2014, of whom 252 (3.0%) were transplanted with octogenarian, brain-dead donor grafts.…”
Section: Dear Editorsmentioning
confidence: 99%